2011
DOI: 10.1111/j.1532-5415.2010.03278.x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Multifactorial Intervention to Reduce Physical Restraints in Nursing Home Residents

Abstract: The intervention reduced restraint use without a significant increase in falling, behavioral symptoms, or medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(102 citation statements)
references
References 29 publications
2
96
2
2
Order By: Relevance
“…A qualitative study about end-of-life care in NHs in UK found that staff expertise about end-of-life care and their strong relationships with residents facilitated end-of-life care for residents with dementia [15]. Also, an interventional study involving education and problem-solving support for Registered Nurses in 45 NHs in German was reported to reduce the use of physical restraints in NH residents [16]. Knowing the characteristics of NH staff in Mainland China will direct areas for future research to improve resident outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…A qualitative study about end-of-life care in NHs in UK found that staff expertise about end-of-life care and their strong relationships with residents facilitated end-of-life care for residents with dementia [15]. Also, an interventional study involving education and problem-solving support for Registered Nurses in 45 NHs in German was reported to reduce the use of physical restraints in NH residents [16]. Knowing the characteristics of NH staff in Mainland China will direct areas for future research to improve resident outcomes.…”
Section: Introductionmentioning
confidence: 96%
“…En experiencias similares en Estados Unidos, Alemania u Holanda, la retirada de sujeciones físicas no supone una reducción significativa en el número ni en la gravedad de las caídas 17,24,25,26,27,28 . Aunque en estos estudios la duración del análisis fue inferior a un año, las muestras eran más grandes, estaban implicados más centros y fueron seleccionados de manera aleatoria 24,29,30 .…”
Section: Discussionunclassified
“…En total en El Puig se pierde un 40% de la población y en Conarda un 37%. Estos porcentajes son similares a las pérdidas por exitus en estudios de similar naturaleza en otros países [17][18] .…”
Section: Aquí Poner Figuraunclassified
“…Despite execution of multifactor intervention and emphasis on the necessity of putting gas pad on the organs before fastening the restraint tools due to failure of the authorities to cooperate and failure to give equipment to the personnel; this standard was not observed in the interven- tion group while it is necessary to fasten organs with gas pad before putting restraint tools and it is regarded as one of the standards of physical restraint (21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%